La (1−x )Ca( x )MnO(3) semiconducting nanostructures: morphology and thermoelectric properties - Culebras, Mario (Springer, 2014)
Semiconducting metallic oxides, especially perosvkite materials, are great candidates for thermoelectric applications due to several advantages over traditionally metallic alloys such as low production costs and high chemical stability at high temperatures. Nanostructuration can be the key to develop highly efficient thermoelectric materials. In this work, La (1−x )Ca( x )MnO(3) perosvkite nanostructures with Ca as a dopant have been synthesized by the hydrothermal method to be used in thermoelectric applications at room temperature. Several heat treatments have been made in all samples, leading to a change in their morphology and thermoelectric properties. The best thermoelectric efficiency has been obtained for a Ca content of x=0.5. The electrical conductivity and Seebeck coefficient are strongly related to the calcium content.